Literasi Participatory Rural Appraisal (PRA) Bersama Komunitas Anak - Albertina N. Lobo; Usman Pakasi; Avelinus Lefaan; Eddy Pattanduk (JURNAL PENGABDIAN PAPUA, 2026)
Child Welfare Institutions (Lembaga Kesejahteraan Sosial Anak/LKSA) provide alternative care, protection, education, and basic social services for children. Beyond meeting basic needs, children in institutional care require opportunities to strengthen participation, self-confidence, independence, and life skills. This community service program aimed to improve Participatory Rural Appraisal (PRA) literacy among children at LKSA Pelangi Abepura, Jayapura, so that they could identify problems, recognize needs and local potential, and design simple productive activities. The program was conducted on 12-18 May 2026 and involved 15 children. Activities comprised social preparation, a pre-test, child-friendly PRA counseling, group identification of needs and assets, product-making practice, packaging design, marketing simulation, reflection, and a post-test. The results showed descriptive improvements in all evaluated aspects. Children's involvement in PRA stages increased from 26.7% to 100%; the ability to identify needs and potential increased from 20% to 100%; understanding of the PRA process increased from 20% to 100%; teamwork increased from 93.3% to 100%; and the ability to design value-added products increased from 73.3% to 100%. These findings indicate that PRA literacy adapted to children's characteristics can facilitate active participation, practical learning, creativity, and basic life-skill development. Continued mentoring is required to maintain these gains and support children's longer-term independence.